Effects of captopril in patients with chronic obstructive pulmonary disease and secondary pulmonary hypertension. Issue 749 (March 1988) - Patakas, D.; Georgopoulos, D.; Rodini, H.; Christaki, P.
Abstract : Ten patients with chronic obstructive pulmonary disease (COPD) with normal left ventricular function were given a single dose of captopril (0.25 mg/kg). Mean systemic arterial pressure, heart rate and coronary flow to the right ventricle were reduced significantly after captopril. In contrast captopril did not cause a significant fall in pulmonary arterial pressure or pulmonary vascular resistance. We conclude that captopril fails to produce haemodynamic benefits in such hypoxic patients and that angiotensin II is not playing a significant role in maintaining pulmonary vasoconstriction.